Consensus definitions for pediatric MS and other demyelinating disorders in childhood. (30th August 2016) - Tardieu, Marc; Banwell, Brenda; Wolinsky, Jerry S.; Pohl, Daniela; Krupp, Lauren B.
Abstract : In light of the published 2012 International Pediatric Multiple Sclerosis Group definitions for pediatric multiple sclerosis (MS) and related disorders and given that pediatric-onset MS is now formally included in the 2010 McDonald criteria for MS, we sought to review these criteria and summarize their application in children with acquired CNS demyelination. In addition, proposals are made for definitions of no evidence of disease activity and inadequate treatment response that are important because of new therapeutic options and trials.